Pengaruh Rentabilitas, Leverage, Dan Saham Bonus Pada Nilai Perusahaan Di Bursa Efek Indonesia - Diani, Ni Wayan Yusy Martha; Astika, Ida Bagus Putra (E-Jurnal Akuntansi; Vol 27 No 3 (2019), 2019)
Firm value in investor’s perspective is the reflection of company’s prospects. One form of firm value is the change in the market price of a company’s stock. This research aims to obtain empirical evidence of the effect of profitability, leverage, and bonus shares on firm value. This research was conducted on companies in all sectors listed on the Indonesia Stock Exchange for the period 2000-2016. The sample selection used purposive sampling technique with non probability sampling method. The population of this research consisted of 37 companies and the number of samples obtained 35 observations. The data in this study was analyzed using the multiple linear regression methods. Based on the results of the research, it can be concluded that profitability has a negative effect on firm value. Leverage has a positive effect on firm value, and bonus shares do not affect firm value. Keywords : Profitability, Leverage, Bonus Shares, and Firm Value